ANALISIS KEPUTUSAN MENTERI PENDAYAGUNAAN APARATUR NEGARA DAN REFORMASI BIROKRASI NOMOR 571 TAHUN 2023 TENTANG OPTIMALISASI PENGISIAN KEBUTUHAN JABATAN FUNGSIONAL TEKNIS PADA PENGADAAN PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA TAHUN ANGGARAN 2022 DARI PERSPEKTIF HUKUM TATA NEGARA - ABDUL KAHAR MARANJAYA (Universitas Mahasaraswati K. Mataram, 2023)
The low graduation rate for the selection participants for the procurement of Government Employees with Work Agreements (PPPK) Technical Functional Positions for the 2022 Budget Year, the Government evaluates the results of the selection which in conclusion needs to give awards for dedication to participants with ex-THK-II and Non ASN status while still guaranteeing the quality of Employees Government with Employment Agreement. There is a Decree of the Minister of Administrative Reform and Bureaucratic Reform Number 571 of 2023 concerning Optimization of Filling the Need for Technical Functional Positions in the Procurement of Government Employees with Work Agreements for the 2022 Fiscal Year, only carried out for positions whose needs have not been met. However, it is very unfortunate that this optimization was carried out only for 2 elements, namely: ex THK-II participants; or Non ASN Participants. Kepmenpan-RB Concerning Optimization has limited participants who are not from Ex THK-II and Non ASN elements from contributing to Government. Apart from being discriminatory, the Kepmenpan-RB Regarding Optimization also cannot guarantee the quality of Government Employees with Work Agreements for Technical Functional Positions for the 2022 Fiscal Year, the results of optimization.